WORKSHOP PEMANFAATAN MEDIA GEOGEBRA UNTUK MENINGKATKAN KEMAMPUAN GURU SMA ALHAIRAT KOTA TERNATE - Hery Suharna; In Hi Abdullah (LP3M STKIP MUHAMMADIYAH MUARA BUNGO, 2023)
This Community Service was carried out at Alkhairat High School, Ternate City. Partner problems namely (1) Teachers experience obstacles in the distance learning process (online); (2) the internet network is not optimal so that it becomes an obstacle in evaluating online learning; (3) Less use of learning media applications has not been utilized optimally; and (4) the teacher experiences difficulties when the teacher uses the application because the teacher lacks knowledge of the application used. This PKM aims to provide solutions for partners, namely Alhairat High School Teachers in Ternate City to improve the ability to use applications in learning. The PKM implementation method is carried out by: (1) Providing material about Geogebra, (2) Learning practices with the Geogebra Application in carrying out learning evaluations, (3) evaluating and mentoring. The results of the PKM that was carried out were (1) the Geogebra Media Utilization Workshop was able to improve the Capability of Alhairat High School Teachers in Ternate City in the Alkhairat High School Hall. Participants who took part were 26 teachers. The results of the participant response sheets stated that the results were very good; and (2) the GeoGebra Media Utilization Workshop has been able to improve the Capabilities of Alhairat High School Teachers in Ternate City like this must continue to be carried out in order to improve teachers' abilities to utilize GeoGebra media in learning, especially for mathematics teachers so that learning has variations in utilizing technology-based learning media.